Facing up to the COVID-19 pandemic in Argentina - Rabinovich, Gabriel Adrián (2021)
From the onset of the SARS-CoV-2 pandemic and following the creation of the ‘Coronavirus Unit’, Argentinean scientists and technologists have contributed by leading basic and translational research initiatives, including developing diagnostic and serological kits, designing new therapeutic approaches, establishing epidemiological platforms, executing clinical trials and implementing social measures to protect the most vulnerable groups of the population.